The Impact of Logging on White-Tailed Deer During the 1800s: Northwoods Wisconsin Case Study - Sheahan, Jeanne Marie (My University, 2001)
The current persistence of white-tailed deer population fluctuations cannot be understood without fully analyzing and appreciating northern Wisconsin's environmental history, particularly logging-induced population fluctuations. The timber industry powerfully illustrates the detrimental, lasting impact of one single human activity on a relatively defenseless species, the white-tailed deer. Wildlife managers, conservationists, politicians, Native Americans, hunters, nature-lovers and citizens, should all take notice of the profound ramifications of logging, which began more than one hundred years ago, and recognize the lasting impacts simple human activities can have on the population dynamics of wildlife species.
Pictures; Maps; Diagrams; Appendices; Bibliography
Keywords: Northwoods; White-tailed deer; Logging